Women in History textbooks - What message does this send to the youth? (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
History textbooks, like all textbooks, play an important role in the facilitation of learning. !ey act as vehicles by means of which past knowledgelegitimated by government and related authorities, as contained in the curriculum, is presented to school-going youth. Textbooks are by naturepowerful and authoritative because they are approved by government and other authorities. As a result, school-going youth are likely to consider theway women and men are portrayed in history textbooks as unquestionable and historically truthful. Having reported on "ndings of empirical studies onwomen in history textbooks from, amongst others, Taiwan; the United States the United Kingdom; Russia and South Africa, we conclude that women areunderrepresented, misrepresented and marginalised in history textbooks.Women are portrayed as historically unimportant and incapable, contributing little to society outside of the domestic sphere. We furthermore argue that thistype of portrayal sends powerful messages to the youth about men and womenin history and in contemporary society
Keywords: History textbooks; Gender; Women; Youth; Females